Chemistry of Pesticides - Roy, N.K; Hadacidin, Thiolutin, Pyrethroids (New Delhi CBS PUBLISHERS & DISTRIBUTORS PVT.LTD.)
This book reveals a detailed discussion on recent developments both on synthetic and natural insecticides, fungicides, pheromones, attractant, repellents etc.
Hadacidin Thiolutin Pyrethroids